Insights into endosomal maturation of human holo‐transferrin in the enteric parasite Entamoeba histolytica: essential roles of Rab7A and Rab5 in biogenesis of giant early endocytic vacuoles. (16th July 2015) - Verma, Kuldeep; Saito‐Nakano, Yumiko; Nozaki, Tomoyoshi; Datta, Sunando
Summary: The pathogenic amoeba E ntamoeba histolytica is one of the causative agents of health hazards in tropical countries. It causes amoebic dysentery, colitis and liver abscesses in human. Iron is one of the essential nutritional resources for survival and chronic infection caused by the amoeba. The parasite has developed multiple ways to import, sequester and utilize iron from various iron‐binding proteins from its host. In spite of its central role in pathogenesis, the mechanism of iron uptake by the parasite is largely unknown. Here, we carried out a systematic study to understand the role of some of the amoebic homologues of mammalian endocytic Rab GTPases (Rab5 and Rab21, Rab7A and Rab7B) in intracellular transport of human holo‐transferrin by the parasite. Flow cytometry and quantitative microscopic image analysis revealed that Rab5 and Rab7A are required for the biogenesis of amoebic giant endocytic vacuoles (GEVs) and regulate the early phase of intracellular trafficking of transferrin. Rab7B is involved in the late phase, leading to the degradation of transferrin in the amoebic lysosome‐like compartments. Using time‐lapse fluorescence imaging in fixed trophozoites, we determined the kinetics of the vesicular transport of transferrin through Rab5‐, Rab7A‐ and Rab7B‐positive compartments. The involvement of Rab7A in the early phase of endocytosis by the parasite marks a significant divergence from its host in terms of spatiotemporal regulation by the Rab GTPases.